Effect of a titanium cage as a stand-alone device on biomechanical stability in the lumbosacral spine of canine cadavers. (February 2017) - Teunissen, M.; van der Veen, A.J.; Smit, T.H.; Tryfonidou, M.A.; Meij, B.P.
Highlights: A stand-alone titanium intervertebral cage was implanted at the lumbosacral junction in canine cadavers. The ex vivo stability of the lumbosacral joint after dorsal laminectomy and discectomy using the cage was determined. Implantation of a stand-alone intervertebral cage restored the disc height and intervertebral foraminal apertures. A stand-alone intervertebral cage is a promising surgical implant for dogs with degenerative lumbosacral stenosis. Abstract: Degenerative lumbosacral stenosis is a common disease in dogs characterised by intervertebral disc herniation, loss of disc height and stenosis. Decompressive dorsal laminectomy and partial discectomy can cause spinal instability and worsen foraminal stenosis. Pedicle screw and rod fixation (PSRF) with an intervertebral body cage allows for distraction and restoration of disc height and restores foraminal apertures. The aim of this study was to evaluate the ex vivo biomechanical properties of a titanium intervertebral cage alone and in combination with PSRF in the lumbosacral spine of dogs. The range of motion, neutral zone, neutral zone stiffness and elastic zone stiffness of the lumbosacral joint (L7-S1) of nine canine cadavers were determined in flexion/extension, lateral bending and axial rotation for four conditions: (1) native (unmodified) spine; (2) dorsal laminectomy and discectomy; (3) stand-alone cage; and (4) cage in combination with PSRF. The intervertebral disc height decreased after dorsal laminectomy, but increased after insertion of the cage. Insertion of the stand-alone cage decreased the range of motion and neutral zone compared to the laminectomy-discectomy and increased neutral zone stiffness in all directions. The range of motion further decreased after PSRF. From a biomechanical point of view, the use of a stand-alone intervertebral cage is a potential alternative to dorsal fixation of the lumbosacral junction, since it increases spinal stability and restores disc height.